DESIGN AND CONSTRUCTION OF A LAB-ON-A-PAPER FOR LOW-COST AND DISPOSABLE POINT-OF CARE DIAGNOSTICS - Afnidar Afnidar; Bambang Kuswandi (Jurnal Sains Dasar, 2016)
Abstract This paper presents a low-cost and disposable paper based microfluidic analysis system for point-of-care diagnostics. Detection is achieved by using a colorimetric or visual indicator. Immobilized specific reagent or enzymes designed for the parameter under consideration act as capture molecules on the surface of the detection zone. The sensor is integrated into a microfluidic system made of paper (cellulose). An additional component of the analysis system is a capillary unit which is used to introduce the analyte to the detection zone. For this purpose well- defined, millimeter-sized channel, comprising hydrophobic polymer bounded onto hydrophilic paper was created. Then the detection zone was coated with a sensitive reagent layer as a sensor region. The paper based microfluidics also called lab on paper, has been fabricated using screen printing technology as the basis for low-cost, disposable, portable and technically simple fabrication for mass production. Microfluidics in paper make it feasible to run single, dual or even multiple clinical analyses on one strip of paper while still using only small volumes of a single sample. The capability of lab on paper for detection of importance clinical analyte protein in urine, saliva and blood samples has been demonstrate successfully. Lab on paper as a diagnostic system is small, disposable, and easy to use and requires no external equipment, reagents, or power sources. This kind of diagnostic system is attractive for use in developing countries, in the field, or as a low-cost alternative to more-advanced technologies already used in clinical diagnostics. Keywords: Lab-on-a-paper, Point-of-care, Visual detection, Clinical diagnostic, Disposable sensor